Analysis The Impact of Southern Thai Malay as a First Language on English Pronunciation toward Science Understanding - Eli Marlina Harahap; Happy Sri Rezeki Purba; Lili Herawati Parapat; Imam Al-Faruq; Isthifa Kemal (Jurnal Penelitian Pendidikan IPA, 2025)
The aims of this research were to analyze the impact of southern Thai Malay on the study of English pronunciation, especially the final consonant sounds. To make the analysis, the researcher used a qualitative method involving 15 students at Ban Kalisa School, Thailand, and data collected by observation, in-depth interviews, and pronunciation tests.  Based on the results related to pronunciation made by 15 students, it can be concluded that there are 1 student pronounced sound [æ] as [a], 1 student pronounced [ʌ] as [u], 3 students pronounced [æ] as [e] and 1 student pronounced [o] as [ʌ]. While in consonant sounds, there are 10 subjects pronounced palate alveolar fricative [ʃ] changed into sound [s, t] or alveolar fricative. 3 students pronounce [ð] with [t], there are 2 students with substitution and 5 students with omission. The students also still have a minor vocabulary in responding to the English questions in an interview. They only knew how to answer the question that related to their identity but had difficulties in responding to the other questions. This research, it is hopefully can be useful to the development of students’ English ability, especially in pronouncing words as one of the indicators of English proficiency.